1985
DOI: 10.2170/jjphysiol.35.57
|View full text |Cite
|
Sign up to set email alerts
|

An increase in cerebral blood flow elicited by electrical stimulation of the solitary nucleus in rats with cervical cordotomy and vagotomy.

Abstract: The effect of monopolar electrical stimulation of the intermediate portion of the solitary nucleus (SOL) on brain circulation was investigated in 48 anesthetized (N2O), artificially ventilated Wistar rats. The cervical spinal cord and bilateral vago-sympathetic trunks were severed to eliminate any change in arterial blood pressure mediated by the autonomic nervous systems on stimulating the SOL. Blood pressure was kept within the physiological range by intravenous phenylephrine infusion. Current intensity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This hypothesis is supported by evidence that baroreflex stimulation modulates the activity of sympathetic fibers innervating the cerebral vessels [14,24] and that electrical stimulation of the nucleus of the solitary tract, the main area onto which baroafferents are projected, increases cerebral blood flow [14]. In addition, sinoaortic denervation, a surgical procedure that disrupts all afferents from the carotid and aortic baroreceptors, eliminates cerebral vasodilatation during acute hypertension induced by the infusion of phenylephrine in anesthetized rats [24].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This hypothesis is supported by evidence that baroreflex stimulation modulates the activity of sympathetic fibers innervating the cerebral vessels [14,24] and that electrical stimulation of the nucleus of the solitary tract, the main area onto which baroafferents are projected, increases cerebral blood flow [14]. In addition, sinoaortic denervation, a surgical procedure that disrupts all afferents from the carotid and aortic baroreceptors, eliminates cerebral vasodilatation during acute hypertension induced by the infusion of phenylephrine in anesthetized rats [24].…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, the thermoregulatory effects mediated by Phy were consequent to the activation of aortic and carotid baroafferents [20], indicating that the increased cutaneous heat loss was not a "pure" thermoregulatory reflex triggered by central cholinergic stimulation. Because baroreflex activation also modulates blood flow in the brain [14,24], icv Phy is also expected to interfere with T brain regulation. However, the effects of Phy on brain thermal homeostasis are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the arterial baroreflex mainly regulates arterial blood pressure such that it is maintained within the range of CA for cerebral circulation. However, anatomically, the autonomic nervous system via arterial baroreflex is directly linked to cerebral circulation (45,51,72,79,80). Several animal studies (45,51,72,79,80) have demonstrated close anatomical locations in the medulla acting as major control sites for both the cerebral and systemic circulation (i.e., the cardiovascular center).…”
Section: Dynamic Systemic Vascular Regulation (Arterial Baroreflex)mentioning
confidence: 99%
“…However, anatomically, the autonomic nervous system via arterial baroreflex is directly linked to cerebral circulation (45,51,72,79,80). Several animal studies (45,51,72,79,80) have demonstrated close anatomical locations in the medulla acting as major control sites for both the cerebral and systemic circulation (i.e., the cardiovascular center). Unilateral electrical stimulation of the nucleus tractus solitarius increased CBF in rats with cervical cordotomy and vagotomy (79), whereas lesions within the nucleus tractus solitarius impaired CA (51).…”
Section: Dynamic Systemic Vascular Regulation (Arterial Baroreflex)mentioning
confidence: 99%
“…Another test to exclude the possible current spreadding towards the fastigial nucleus was made by observing the vasopressin-induced pressor response when the nucleus was ablated. After ablation of the median one-third of the cerabellum (see NAKAI, 1985, for an illustration), electrical stimulation of 8 positions within the SOL still elicited the pressor response (see NAKAI, 1985, for a typical record). Vol.…”
Section: Resultsmentioning
confidence: 99%